The Impact of Work-Life Balance on Employee Performance and Satisfaction in Start-Up Companies - Nugroho, Dony Ari (The Islamic Education and Multiculturalism Foundation, 2025)
As of January 11, 2024, Indonesia has 2,566 startups, ranking sixth in the world and first in Southeast Asia. Startups in Indonesia focus on technological innovation with the goal of rapid growth, often funded by venture capital or crowdfunding. Despite facing financial challenges and competition, startups have the potential to disrupt industries. However, they also face challenges in maintaining operational balance and employee well-being, which impacts performance and satisfaction. The aim of this research is to analyze the extent to which the balance between work and personal life affects employee performance and satisfaction in startup companies. This study uses a quantitative method with data collection through questionnaires. The population of the study consists of employees from startup company X, with a sample selected using purposive sampling, resulting in 100 respondents. The data collected was analyzed using SPSS for statistical analysis and hypothesis testing to present objective and accurate research results. The findings show that work-life balance positively influences employee performance and satisfaction in startup companies. Employees who are able to balance work and personal life tend to be more productive and satisfied, as this balance reduces stress, increases motivation, and improves well-being. Therefore, startup companies need to create an environment that supports work-life balance to enhance employee performance and satisfaction.